Singular parabolic equations, measures satisfying density conditions, and gradient integrability. (April 2017) - Baroni, Paolo
Abstract: We consider solutions to singular parabolic equations with measurable dependence on the ( x, t ) variables and having on the right-hand side a measure satisfying a density condition. We prove that the less the measure is concentrated, the more the gradient is regular, in the Marcinkiewicz scale. We provide local estimates and recover some classic results.